О точных оценках поточечного приближения алгебраическими многочленами классов WrHω - Моторный, В.П. (Український математичний журнал, 2001)
Одержано оцінки наближення функцій класу W^rH^ω (ω(t) — опуклий модуль неперервності, такий, що tω'(t) не спадає) алгебраїчними многочленами з урахуванням положення точки на відрізку [—1,1], які неможливо покращити одночасно для всіх модулів неперервності. We obtain estimates for the approximation of functions of the class W^rH^ω, where ω(t) is a convex modulus of continuity such that tω′(t) does not decrease, by algebraic polynomials with regard for the position of a point on the segment [−1, 1]. The estimates obtained cannot be improved for all moduli of continuity simultaneously.